2022
DOI: 10.3389/fgene.2022.823182
|View full text |Cite
|
Sign up to set email alerts
|

Ginsenoside Rg3 Alleviates Cisplatin Resistance of Gastric Cancer Cells Through Inhibiting SOX2 and the PI3K/Akt/mTOR Signaling Axis by Up-Regulating miR-429

Abstract: Platinum-based cytotoxic chemotherapy is considered the standard treatment for advanced gastric cancer (GC). However, cisplatin chemoresistance often occurs with the mechanisms being not well clarified, which results in the cancer recurrence and poor survival. Ginsenoside Rg3, isolated from the Chinese Herb Panax Ginseng, is recognized as an anti-cancer agent. Herein, we aimed to reveal whether Ginsenoside Rg3 alleviates cisplatin resistance and sensitizes GC cells to cisplatin-induced apoptosis, and draw out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…The use of ginsenoside Rg3 may contribute to reducing toxicity and improving chemosensitivity in cancer combination therapy [ 204 ]. It was found that ginsenoside Rg3 reduced cisplatin resistance by upregulating miR-429 to inhibit the SOX2 and PI3K/Akt/mTOR signaling axes in gastric cancer treatment [ 30 ]. In pancreatic cancer treatment, ginsenoside Rg3 regulated the survival of pancreatic cancer cells via the PI3K/Akt/mTOR pathway [ 205 ].…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…The use of ginsenoside Rg3 may contribute to reducing toxicity and improving chemosensitivity in cancer combination therapy [ 204 ]. It was found that ginsenoside Rg3 reduced cisplatin resistance by upregulating miR-429 to inhibit the SOX2 and PI3K/Akt/mTOR signaling axes in gastric cancer treatment [ 30 ]. In pancreatic cancer treatment, ginsenoside Rg3 regulated the survival of pancreatic cancer cells via the PI3K/Akt/mTOR pathway [ 205 ].…”
Section: Natural Products In Preventing Tumor Drug Resistancementioning
confidence: 99%
“…For example, matrine can improve the sensitivity of resistant cancer cells to chemotherapeutic drugs by reactivating apoptosis and inhibiting drug efflux [ 26 ]; Tetrandrine can fight the multiple-drug resistance (MDR) of cancer cells by downregulating the expression of ABCB1 transporters [ 27 ]; quercetin can reverse the resistance of paclitaxel-resistant prostate cancer cells in vitro by reversing activation of the androgen receptor and PI3K/Akt signaling [ 28 ]. Osthole reverses the chemotherapeutic resistance of cisplatin-resistant cervical cancer cells by inactivating the PI3K/AKT pathway [ 29 ]; and ginsenoside Rg3 can inhibit the mTOR signaling axis of SOX2, PI3K/Akt, and miR-429 to reduce the resistance to cisplatin [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since miR-200 family miRNAs are mostly decreased in anti-cancer drug-resistant cells compared to parental sensitive cells, it is necessary to develop therapeutic miR-200 family miRNA-mimics (miR-200-mimics) that can overcome the resistance to anti-cancer drugs. The overexpression of miR-200 family miRNAs has been reported to enhance chemosensitivity [ 107 , 108 , 111 ]. Drugs targeting miR-200 family-regulated genes can be combined with miR-200 family miRNA-mimics to overcome the resistance to anti-cancer drugs.…”
Section: Discussionmentioning
confidence: 99%
“…SOX2 is known to be a target of the miR-200 family in colorectal cancer [ 110 ]. miR-429 enhanced the sensitivity of gastric cancer cells to cisplatin by decreasing the expression of SOX2 and inhibiting PI3K/Akt/mammalian target of rapamycin (mTOR) signaling [ 111 ]. These reports further indicate the role of cancer stem cells in anti-cancer drug resistance.…”
Section: Role Of the Mir-200 Family In Anti-cancer Drug Resistancementioning
confidence: 99%
“…Wang et al observed that β-elemene induces cell cycle arrest in the G2/M phase by regulating the ROS/AMPK/mTOR pathway ( Wang X et al, 2022 ).…”
Section: Anti-tumor Mechanism Of Action Of the Active Ingredients Of ...mentioning
confidence: 99%